The financial transmission of housing bubbles: Evidence from Spain - Alberto Martin; Enrique Moral-Benito; Tom Schmitz (European Central Bank (ECB), 2019)
How do housing bubbles affect other economic sectors? We show that in the presence of collateral constraints, a bubble initially raises housing credit demand and crowds out credit to non-housing firms. If the bubble lasts, however, housing credit repayments raise banks' net worth and expand credit supply, so that crowding-out eventually gives way to crowding-in. This is consistent with evidence from the recent Spanish housing bubble. Initially, credit growth of non-housing firms was lower at banks with higher bubble exposure, and firms relying on these banks exhibited lower credit and output growth. During the bubble's last years, these effects reversed.
Keywords: E32; E44; G21; 330; Housing bubble; Credit; Investment; Financial Frictions; Financial Transmission; Spain